Resistive Traits of the Tunisian Medina Bazaars' Architectural Spaces in the Globalized World - Tira, Yasmine; Canbay Turkyilmaz, Cigdem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
In ancient times, bazaars were an integral part of the city life; bifurcating from the city structure and reflecting each period of time's architectural characteristics. It is also said that they are the source of 20 communications and trade activities. However, due to the quick changes in the cities' spatial configurations that we are living in, these traditional spaces started to run a risk of possible cultural continuity alteration. But, despite the disturbing contradiction which is affecting their traditional allure, they still reflect an undying identity. They are still talking about the engraved cultural memory thro ugh several architectural traits and spatial experiences. This paper aims to highlight the significance of the 25 Medina of Tunis bazaars' resistance against globalization. The present study case analysis lead to a conceptual framing of cultural continuity's model being a tripartite relation between identity, heritage and collective memory. Through this research, it had been concluded that several resistance traits witness that the Medina of Tunis is still showing a cultural continuity able to counter the market capitalization.
Keywords: Cultural continuity; globalization; identity; traditional bazaars; Architecture